Application and Research Progress of Cementitious Filling with Industrial Solid Wastes in Mine - Xiaomei WAN; Hui LI; Yaguang ZHU; Yunzheng CUI; Ya CHEN (Kuangchan zonghe liyong)
The application and research of cementitious filling with industrial solid waste in mines in China are summarized and analyzed in this paper. The industrial solid waste based cementitious filling materials are divided into slag based cementitious filling materials, fly ash based cementitious filling materials, coal gangue based cementitious filling materials and red mud based cementitious filling materials. The industrial solid waste based cementitious filling materials are analyzed from three aspects of activation mechanism, mechanical properties and working performance. It is pointed out that the development of solid waste resources to prepare mine filling materials according to local conditions and the development of full solid waste filling materials are the important development directions of mine cementitious filling research in the future.